Epidural Analgesia for Labor and Delivery in a Patient with von Willebrand's Disease. Issue 2 (March 1989) - Cohen, Shaul; Daitch, Jonathan S.; Amar, David; Goldiner, Paul L.
Abstract : Patients with histories of bleeding disorders may still benefit from regional anesthetic techniques. The decision to perform the block should be individualized, based on coagulation tests. The authors describe a patient with von Willebrand's disease in whom pregnancy itself improved factor VIII activity, enabling performance of an epidural block for labor and delivery.